A multidimensional analysis of strategies for the enhancement of railway freight capacity and their effects on the sustainability of transportation infrastructure - a case study of China-Pakistan economic corridor (CPEC) - Muhammad Bilal Khurshid; Usama Khan; Jamal khan; Muhammad Asif Khan (Mehran University Research Journal of Engineering and Technology)
Current imbalance in freight share (96% roads vs. 4% railways) in Pakistan, is impacting the performance of highways and is causing under-utilization of existing railway network. Expected increased freight demand due to China-Pakistan Economic Corridor (CPEC), necessitates a strategic shift towards multimodal freight transportation. With this background, this research provides a multidimensional analysis of strategies to enhance Pakistan Railways (PR) freight capacity by shifting calculated freight load from highways under CPEC scenario and examines their effects on the sustainability of transportation infrastructure owing to reduction in highways maintenance and rehabilitation (M&R) expenditure. Addressing the crucial issue of over-reliance on roads for freight transportation, this research employs economic indicators in statistical modeling to forecast freight demand. Three strategic railway freight capacity enhancement options have been proposed for 2025 and 2030. This study highlights that PR would be able to accommodate up to 24.07% of total freight by 2025 without compromising railway passenger load. Additionally, this study reveals that if the current freight share distribution remains unchanged, then highways M&R expenditure is expected to be increased by over 84%, by the year 2025, compared to the year 2015. However, highways M&R expenditure is expected to be reduced by 78.77% and 60.56% by the year 2025 and 2030, respectively, basing on the proposed freight load distribution strategies. This study would be highly beneficial for transportation agencies in optimal freight transportation management while ensuring efficient sustainability of transportation infrastructure, especially for the countries that have a high dependency on roads for freight transportation.